FAKTOR-FAKTOR PENENTU PERILAKU PENCARI KERJA TERHADAP REKRUTMEN ONLINE DI MASA PANDEMI - Theo Wicaksono; Fuad Mas’ud (Jurnal Akuntansi dan Pajak, 2023)
With the COVID-19 pandemic, people must be more familiar with the use of technology and the internet, including the recruitment system. Many companies need new employees but are hindered by restrictions on community activities, so they cannot carry out the recruitment process directly. To attract public interest, especially Diponegoro University graduate students, in participating in online recruitment, researchers want to know what factors influence job seekers when accessing online recruitment. Data were collected using a questionnaire and processed using a linear regression method. The results obtained are that the quality of information, website vividness, interactivity, attractiveness effectiveness, and search engine optimization have a positive and significant effect on the behavior of job seekers in Semarang in participating in online recruitment. Keywords: human resource management, job seeker behavior, linear regression, online recruitment